2016
DOI: 10.1098/rsbl.2016.0466
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice, rain-on-snow and tundra reindeer nomadism in Arctic Russia

Abstract: Sea ice loss is accelerating in the Barents and Kara Seas (BKS). Assessing potential linkages between sea ice retreat/thinning and the region's ancient and unique social–ecological systems is a pressing task. Tundra nomadism remains a vitally important livelihood for indigenous Nenets and their large reindeer herds. Warming summer air temperatures have been linked to more frequent and sustained summer high-pressure systems over West Siberia, Russia, but not to sea ice retreat. At the same time, autumn/winter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 26 publications
2
137
0
Order By: Relevance
“…Increased frequency of the rain-on-snow in recent years across the southern Spitsbergen is an important indicator of on-going climate change, also in other sectors of the Arctic [38,39,48]. RoS events started to be the indirectly investigated in the Hornsund area as early as the 1980s [49].…”
Section: Discussionmentioning
confidence: 99%
“…Increased frequency of the rain-on-snow in recent years across the southern Spitsbergen is an important indicator of on-going climate change, also in other sectors of the Arctic [38,39,48]. RoS events started to be the indirectly investigated in the Hornsund area as early as the 1980s [49].…”
Section: Discussionmentioning
confidence: 99%
“…Icing events, which result in malnutrition and starvation, have been associated with catastrophic die-offs of Rangifer (but see Tyler 2010) and other ungulates (Forchhammer and Boertmann 1993;Putkonen and Roe 2003). These events have particular significance in the High Arctic among Peary caribou (Miller and Gunn 2003;Tews et al 2007a;Miller and Barry 2009;Langlois et al 2017) and Svalbard reindeer (Kohler and Aanes 2004;Hansen et al 2014), but they have also been observed in semi-domesticated reindeer populations in Scandinavia (Heggberget et al 2002;Putkonen and Roe 2003) and Russia (Bartsch et al 2010;Forbes et al 2016). Noncatastrophic rain-on-snow and icing events have negative associations with body condition (Bartsch et al 2010;Loe et al 2016) and reproductive success (Helle and Kojola 2008;Stien et al 2012) in caribou and reindeer.…”
Section: Extreme Weather and Icing Eventsmentioning
confidence: 99%
“…Caribou calves <1 month in age, however, have higher survival rates in years with earlier snowmelt (Griffith et al 2002), although all resident grazing species in the Arctic (e.g., caribou, reindeer, muskox, voles, etc.) are vulnerable to rainon-snow events during winter that can render their forage inaccessible (Stien et al 2012;Forbes et al 2016). Offshore, earlier trends in sea ice melt onset (Stroeve et al 2014) have contributed to unprecedented sea ice losses in late summer, which in turn have altered the seasonal noting that the prevailing October onshore winds are from the east-northeast (onshore) and that Utqiaġvik is a coastal location.…”
Section: Ecological Responses To Changing Seasonalitymentioning
confidence: 99%